Malaysian foreign policy orientation and relations in the Post-Mahathir years - Md Khalid, K. (2009)
Malaysian foreign policy under Mahathir (1981-2003) has been described as independent, active and pragmatic. Two decades of Mahathir’s leadership have resulted in Malaysia becoming more internationally recognised as a model of stable, multicultural and developing country with a relatively impressive economy. Malaysia was also regarded as an exemplary progressive and moderate Islamic country. While the importance of trade and investment was evident as the basis of Malaysia’s external ties with many countries (including the Commonwealth of Independence States – CIS), other factors which included religion (Islam) in the context of multiculturalism also became significant determinants. In effect, Malaysia’s international image has, undoubtedly, been promoted and enhanced by many of Mahathir’s bold and innovative policy initiatives. However, foreign policy under Abdullah Badawi was rather lacklustre due to preoccupation with domestic challenges such as intra-UMNO/ BN bickering (including the MCA) and the growing influence of the Opposition coalition led by Anwar Ibrahim. Despite the lack of focus, Abdullah succeeded in thawing relations with Singapore, and Malaysia attracted the attention of the US as a progressive Islamic nation with the Islam Hadhari brand. This paper argues the need for Malaysia to bolster its international image and standing through new foreign policy initiatives which are relevant and responsive to the changing dynamics of the domestic as well as the regional and global political economy. Set against the backdrop of a more demanding political scenario and recessionary global economy, the paper contends that Malaysia should reprioritise and reposition its foreign policy direction and initiatives to leverage on more focussed relations with key countries, namely the US and China (PRC). This should be part of Najib’s strategy to reclaim political legitimacy and ensure economic transformation on the basis of his guiding philosophy of ‘1Malaysia, People First, Performance Now’.